The impact of aging on intestinal mucosal immune function and clinical applications - Zheng, Han; Zhang, Chi; Wang, Qianqian; Feng, Shuyan; Fang, Yi; Zhang, Shuo (Frontiers in Immunology, 2022)
Immune cells and immune molecules in the intestinal mucosa participate in innate and adaptive immunity to maintain local and systematic homeostasis. With aging, intestinal mucosal immune dysfunction will promote the emergence of age-associated diseases. Although there have been a number of studies on the impact of senescence on systemic immunity, relatively fewer studies have been conducted on the impact of senescence on the intestinal mucosal immune system. In this review, we will briefly introduce the impact of senescence on the intestinal mucosal barrier, the impact of senescence on intestinal immune cells as well as immune molecules, and the process of interaction between intestinal mucosal immunity and gut microbiota during aging. After that we will discuss potential strategies to slow down intestinal senescence in the elderly.